1999
DOI: 10.3109/07357909909021429
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Lesions of Metastatic Visceral Malignancy Mimicking Pyogenic Granuloma

Abstract: Cutaneous metastases may be the first sign of a previously undiagnosed visceral malignancy or the initial presentation of a recurrent neoplasm. Rarely, skin metastases can resemble a pyogenic granuloma. Three oncology patients who developed new pyogenic granuloma-like cutaneous lesions are described. Histopathologic examination showed metastatic visceral malignancy in the skin. The characteristics of the previously reported cancer patients with metastatic tumor to the skin that mimicked a pyogenic granuloma ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…8 One study found that 1% of genitourinary tumors will metastasize to skin, and of those, most are renal cell carcinomas. 6 Another found that the rate of cutaneous metastases from renal cell carcinoma was 3.3%, but this series included a smaller number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 One study found that 1% of genitourinary tumors will metastasize to skin, and of those, most are renal cell carcinomas. 6 Another found that the rate of cutaneous metastases from renal cell carcinoma was 3.3%, but this series included a smaller number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, cutaneous metastatic disease has not been reported in renal medullary carcinoma. [6][7][8][9][10][11] Here, we present the first case of renal medullary carcinoma metastatic to the scalp.…”
Section: Introductionmentioning
confidence: 93%
“…Other diagnoses such as angioma tuft, hemangioma, lobular angioma, micro capillary angioma, Masson tumors, reactional angioendotheliomatosis, angiokeratoma and bacillary angiomatosis [6, 7] could draw our attention in front of this kind of image. These observations prompt us to think directly to bacterial culture and histological examination as key for the diagnosis of this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] When affecting the fingers, the distal phalanx of the third finger appears to be the site most commonly affected for reasons that remain to be clarified. [3][4][5][6][7][8] In the present case, the patient had a lytic lesion, with bone absorption affecting almost the entire distal phalanx; however, the affected finger was the fourth rather than the third finger. In addition, there was a skin lesion, albeit without bone involvement, on the fourth finger of the contralateral hand.…”
Section: Discussionmentioning
confidence: 99%